Institutional Sustainability Analysis of Community-Based Tourism (Case of Kasbi Community in North Halmahera ) - Singgalen, Yerik Afrianto; Sasongko, Gatot; Wiloso, Pamerdi Giri (Sodality: Jurnal Sosiologi Pedesaan, 2018)
This study aims to analyze the sustainability of the implementation of the concept of community-based tourism especially in the Tourism Community in North Halmahera Regency known as "Kasbi". The research method used is qualitative with a case study approach. The results of this study indicate that contextually in North Halmahera Regency, participation and partnership are very essential in achieving sustainability in the implementation of the concept of community-based tourism. Thus, local tourism institutions need support from various stakeholders to achieve sustainable development goals.